2021
DOI: 10.3389/fmicb.2021.738371
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Novel Sequence Types of Carbapenem-Resistant Acinetobacter baumannii, With Heterogeneous Resistance Determinants and Targeted Variations in Efflux Operons

Abstract: Acinetobacter baumannii has emerged as one of the dominant nosocomial human pathogens associated with high morbidity and mortality globally. Increased incidences of carbapenem-resistant A. baumannii (CRAB) have resulted in an enormous socioeconomic burden on health-care systems. Here, we report the genotypic and phenotypic characterization of novel ST1816 and ST128 variants in A. baumannii strains belonging to International clone II (GC2) with capsule types KL1:OCL8 and KL3:OCL1d from India. Sequence analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…ATCC 27244, and A. baumannii ATCC 19606 are highly sensitive to 5-fluoroorotic acid. This finding is consistent with a previous study that found that the A. baumannii strains DR2 and AB067 were also sensitive to 5-fluoroorotic acid [ 17 ]. Importantly, human cell lines (HT-1080, IMR-90, HeLa S3, and HL-60) and a mouse cell line (L-1210) have been shown to be relatively tolerant of 5-fluoroorotic acid [ 18 ], indicating that 5-fluoroorotic acid could be used to treat infections in patients.…”
Section: Discussionsupporting
confidence: 93%
“…ATCC 27244, and A. baumannii ATCC 19606 are highly sensitive to 5-fluoroorotic acid. This finding is consistent with a previous study that found that the A. baumannii strains DR2 and AB067 were also sensitive to 5-fluoroorotic acid [ 17 ]. Importantly, human cell lines (HT-1080, IMR-90, HeLa S3, and HL-60) and a mouse cell line (L-1210) have been shown to be relatively tolerant of 5-fluoroorotic acid [ 18 ], indicating that 5-fluoroorotic acid could be used to treat infections in patients.…”
Section: Discussionsupporting
confidence: 93%